2019
DOI: 10.1002/ejic.201900584
|View full text |Cite
|
Sign up to set email alerts
|

Toward Metal–Organic‐Framework‐Based Supercapacitors: Room‐Temperature Synthesis of Electrically Conducting MOF‐Based Nanocomposites Decorated with Redox‐Active Manganese

Abstract: Nanocrystals of a zirconium-based metal-organic framework (Zr-MOF) were grown on carboxylate-functionalized carbon nanotubes (CNT) at room temperature to synthesize electrically conducting Zr-MOF-CNT nanocomposites. To further enable charge transport within the Zr-MOF phase via redox hopping under electrochemical conditions, redox-active manganese sites were then installed in the Zr-MOF and nanocomposites at room temperature by means of the solvothermal deposition in MOFs (SIM) technique. The redox hopping beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(109 citation statements)
references
References 71 publications
22
87
0
Order By: Relevance
“…Thus, a variety of aforementioned published studies applying pristine MOFs for electroanalysis utilized MOFs constructed by redox‐active moieties and relied on redox hopping to transport electrons during the electroanalytical processes. However, several studies have indicated that the redox hopping in pristine MOFs is not efficient enough to achieve sufficiently remarkable electrochemical performances . It should be noted that the redox hopping in pristine MOFs is coupled with both the electron transport and the diffusion of ionic species within the frameworks .…”
Section: Charge Transport In Mofsmentioning
confidence: 99%
“…Thus, a variety of aforementioned published studies applying pristine MOFs for electroanalysis utilized MOFs constructed by redox‐active moieties and relied on redox hopping to transport electrons during the electroanalytical processes. However, several studies have indicated that the redox hopping in pristine MOFs is not efficient enough to achieve sufficiently remarkable electrochemical performances . It should be noted that the redox hopping in pristine MOFs is coupled with both the electron transport and the diffusion of ionic species within the frameworks .…”
Section: Charge Transport In Mofsmentioning
confidence: 99%
“…Then, 6 mg of Mo-SIM-MOF-808 was dispersed in 0.5 mL of acetone by sonication, and 6 μL of the resulting suspension was casted on the exposed Ti substrate by a micropipette; similar drop-casting processes of other Zr-MOF thin films have been reported in our previous studies. 47,62 Thereafter, the obtained Mo-SIM-MOF-808 thin film deposited on the Ti foil was used as the working electrode in an aqueous 0.05 M MOPS buffer solution (pH = 7.3), and 30 cycles of cyclic voltammetric (CV) scan between 0 V and −1.0 V vs Ag/AgCl/ NaCl (3 M) was performed at a scan rate of 50 mV/s to reduce Mo(VI) to metallic molybdenum. The obtained thin film was designated as "Mo@MOF-808" and was directly used for electrochemical measurements.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The Mn-decorated Zr-MOFcarbon nanotube nanocomposite (Mn-30CNT-UiO-66), which was used as the material for the positive electrodes, was synthesized according to the procedure reported in our recent work. 47 The dropcasting process which is the same as that for Mo-SIM-MOF-808 was utilized to deposit the thin film of Mn-30CNT-UiO-66 on a Ti substrate. The tapes used to control the exposed geometric area for the drop-casting and electrochemical processes were removed from both the Mo@MOF-808 and Mn-30CNT-UiO-66 electrodes to obtain both thin films on Ti foils with the same area (0.25 cm 2 ).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The specific surface areas of the as-synthesized O–CNT/NiFe increased from 72.3 to 110.5 m 2 g –1 by increasing the amounts of CNTs from 1:27 to 1:6. The increased specific surface area of O–CNT/NiFe is mainly contributed by the higher BET surface area of CNTs (∼285 m 2 g –1 ), not from O–NiFe (64.3 m 2 g –1 ). Moreover, the pore size distributions of CNT/NiFe 1:18 and O–CNT/NiFe 1:18 were further studied and compared.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, oxygen plasma treatment is able to tune the oxygen functional groups on the surface of CNTs, which is expected to influence the electrocatalytic activities as a result of different electronic properties. Notably, the O 1s peak of O−CNT (Figure 3d (∼285 m 2 g −1 ), 52 not from O−NiFe (64.3 m 2 g −1 ). Moreover, the pore size distributions of CNT/NiFe 1:18 and O−CNT/ NiFe 1:18 were further studied and compared.…”
Section: ■ Introductionmentioning
confidence: 99%